Adaptations to swimming training: influence of training volume - Costill, D. L.; Thomas, R.; Robergs, R. A.; Pascoe, D.; Lambert, C.; Barr, S.; Fink, W. J. (Medicine & Science in Sports & Exercise, 1991)
An attempt was made to assess the contributions of increased training volumes on swimming performance. Two matched groups of college male swimmers were studied before and during a 25-week training period with different volumes. Implications: The changes in endurance that occurred in the first eight weeks were independent of the training load (they were similar for both groups). From then on, there was no appreciable change in endurance fitness. One has to question the value of excessive training for sprinters if speed is reduced as was demonstrated in this study. These findings may not be applicable to age-group (< 16 yrs) or female swimmers. In considering the lack of demonstrated effects that are generally attributed to increased training by coaches the authors suggest: .. . our knowledge of the need for specificity in training might lead us to assume that such training may not provide the adaptations needed for optimal swimming performance. Since the majority of the competitive swimming events last less than 3 min, it is difficult to understand how training at speeds that are markedly slower than competitive pace for 3-4 hr/day will prepare the swimmer for the supramaximal efforts of competition.